Interconversion of tetrahedral [(M)(4)boolean ANDMg-4(L-1)(6) - Bauer, Walter; Maid, Harald; Saalfrank, Rolf W. (European Journal of Inorganic Chemistry)
In this review we report on the enantiomerization of tetrahedral racemic-[(NH4)(4) boolean ANDMg-4(L-1)(6)] monitored by means of variable temperature (VT) H-1 NMR spectroscopy. The enantiotopization of the diastereotopic protons is due to simultaneous Bailar twists at the four octahedrally coordinated magnesium centres, synchronized with atropisomerization of the six edge-bridging ligands (L-1)(2-).The VT H-1 NMR spectrum of tetrahedral meso-[In-4(L-2)(4)] is coined through the helicity of the four face-centred tripodal hexadentate ligands (L-2)(3-) and can, alike the H-1 NMR of cyclic meso-[In6Cl6(L-3)(6)], be explained by the enantiotopization of the diastereotopic protons via mesomerization.
CRIS-Team WoS Importer:2021-12-10